2008
DOI: 10.1073/pnas.0804723105
|View full text |Cite
|
Sign up to set email alerts
|

Optical methodology for detecting histologically unapparent nanoscale consequences of genetic alterations in biological cells

Abstract: Recently, there has been a major thrust to understand biological processes at the nanoscale. Optical microscopy has been exceedingly useful in imaging cell microarchitecture. Characterization of cell organization at the nanoscale, however, has been stymied by the lack of practical means of cell analysis at these small scales. To address this need, we developed a microscopic spectroscopy technique, single-cell partial-wave spectroscopy (PWS), which provides insights into the statistical properties of the nanosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
208
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(222 citation statements)
references
References 29 publications
(41 reference statements)
14
208
0
Order By: Relevance
“…The preparation of these cells is described elsewhere. 8 Both HT29 cells and their CSK construct cells underwent a standard sample preparation protocol for TEM imaging, including fixing, staining, embedding, sectioning and, finally, performing TEM imaging, as described earlier for the nanoparticles. 7 Figures 3͑a͒ and 3͑b͒ show representative TEM grayscale images of HT29 cells and CSK constructs.…”
Section: Fig 2 ͑Color͒ ͓͑A͒-͑d͔͒mentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of these cells is described elsewhere. 8 Both HT29 cells and their CSK construct cells underwent a standard sample preparation protocol for TEM imaging, including fixing, staining, embedding, sectioning and, finally, performing TEM imaging, as described earlier for the nanoparticles. 7 Figures 3͑a͒ and 3͑b͒ show representative TEM grayscale images of HT29 cells and CSK constructs.…”
Section: Fig 2 ͑Color͒ ͓͑A͒-͑d͔͒mentioning
confidence: 99%
“…In our most recent optical experiments, we show that the degree of nanoscale disorder increases with the degree of carcinogenesis for both control and precancerous cells ͑in cell lines, mouse model, and different organs in human studies, such as pancreas, colon, and lung͒. [8][9][10] These nanoscale changes may result from the rearrangements of DNA, RNA, lipids, or proteins. We want to verify and quantify these nanoscale changes as observed in optical studies by TEM.…”
mentioning
confidence: 99%
“…The method was used to reliably identify genetic alterations in cancer cell lines. 27,28 Clinical studies demonstrated the sensitivity of PWS in detecting pancreatic cancer, colon cancer, and lung cancer, with a novel approach for cancer screening by detecting the field effect of carcinogenesis. 29 An alternate explanation of the nanoscale sensitivity of this measurement was recently presented by making use of the Born approximation and comparing the results with finite-difference time-domain (FDTD) simulations of the microscope with randomly generated refractive index distributions as the numerical samples.…”
mentioning
confidence: 99%
“…PWS microscopy achieves sensitivity to nanoscale structures within biological cells by using the spectroscopic content of microscope images, and quantitatively measures nanoarchitectural changes in cells associated with carcinogenesis [6,7]. These intracellular, macromolecular alterations are recognizable as some of the earliest indicators of carcinogenesis and are detectable throughout an affected organ, not just at the tumor site, via a phenomenon known as the field effect of carcinogenesis [8,9].…”
Section: Introductionmentioning
confidence: 99%